Prevalence of methicillin-resistant Staphylococcus aureus in dairy farms: A systematic review and meta-analysis - Khanal, Shrijana; Boonyayatra, Sukolrat; Awaiwanont, Nattakarn (Frontiers in Veterinary Science, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) is an opportunistic bacterium that causes many human and animal infections worldwide. MRSA infections are classified as priority infections owing to their high morbidity and mortality, with a significant risk of zoonotic transmission. This study aimed to determine the pooled prevalence of MRSA in dairy cattle farms and its heterogeneity. Relevant studies were retrieved from three databases, PubMed, Web of Science, and Scopus. The pooled prevalence of MRSA in dairy farms was estimated using a random-effects model. Subgroup and meta-regression analyses were used to assess the probable sources of heterogeneity. Sensitivity and publication bias analyses were also performed. A total of 108 articles were eligible for inclusion in this meta-analysis. The pooled prevalence of MRSA was estimated to be 4.12% (95% confidence interval [95% CI]=2.86 to 5.57) with significantly high heterogeneity (I2=98.1%, p=0.00). For the subgroup analysis among continents, the prevalence was highest in Asia (5.56%; 95% CI=3.56 to 7.96) and lowest in North America (0.91%, 95% CI=0.00 to 4.99). As for the year of publication, MRSA prevalence was highest in reports published from 2015 to 2018 (4.98%, 95% CI=2.76 to 7.78) and lowest in reports published before 2015 (3.67%, 95% CI=1.33 to 7.01). As for sample type, the prevalence of MRSA in cattle milk (4.02%, 95% CI=2.76 to 5.49) was lower than that in other sample types (5.05%, 95% CI=1.71 to 9.69). These three factors were not significantly associated with the pooled prevalence of MRSA (p>0.05). Therefore, the findings of this study indicate that the prevalence of MRSA has been minimal and consistent in dairy cattle farms over the past two decades.